2001
DOI: 10.1097/00004647-200103000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Metabotropic Glutamate Receptor System Protects against Ischemic Free Radical Programed Cell Death in Rat Brain Endothelial Cells

Abstract: As one of the key determinants of ischemic injury, cerebrovascular endothelial cell (EC) degeneration may be dependent upon the generation of the free radical nitric oxide (NO) and the subsequent induction of programmed cell death (PCD). Although the mechanisms that can prevent EC injury are most likely multifactorial in origin, the metabotropic glutamate receptor (mGluR) system may represent a novel therapeutic approach for ECs given the ability of the mGluR system to reverse neuronal cell injury. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(159 citation statements)
references
References 49 publications
6
153
0
Order By: Relevance
“…Neurons and glia are commonly recognized as the major targets for glutamate in the brain, but the existence of functional GluRs in cerebral vasculature has been long debated. However, the vast body of evidence accumulated over the recent years clearly demonstrates that GluRs are expressed in cerebral vascular endothelium and contribute to the endothelial functions in rats, humans, and newborn pigs [61,[84][85][86][87][88].…”
Section: Glutamate Receptors In Cerebral Vascular Endothelium and Ho-mentioning
confidence: 99%
“…Neurons and glia are commonly recognized as the major targets for glutamate in the brain, but the existence of functional GluRs in cerebral vasculature has been long debated. However, the vast body of evidence accumulated over the recent years clearly demonstrates that GluRs are expressed in cerebral vascular endothelium and contribute to the endothelial functions in rats, humans, and newborn pigs [61,[84][85][86][87][88].…”
Section: Glutamate Receptors In Cerebral Vascular Endothelium and Ho-mentioning
confidence: 99%
“…Furthermore, oxidative stress can significantly increase chromosomal aberrations and micronuclei [26,39] and lead to the activation of apoptotic pathways in ECs [38,116,193]. ECs that are exposed to oxidative stress incur both DNA fragmentation and membrane PS externalization during exposure to insults, such as hypoxia, oxidants, and free radicals [9,28,38,39,124].…”
Section: Alzheimer's Disease In the Aging Populationmentioning
confidence: 99%
“…Cytoprotection by the mGluR system is believed to act at or below the level of free radical generation and oxidative stress [143,192,236]. More recent work has suggested that mGluR offers similar protective capacity to the vascular system by preventing endothelial cell DNA degradation, caspase activity, and inhibiting a thrombotic state through the maintenance of membrane asymmetry [125,124,142].…”
Section: Modulation Of the Metabotropic Glutamate Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, oxidative stress can significantly increase chromosomal aberrations and micronuclei (Bresgen, N et al, 2003 and lead to the activation of apoptotic pathways , Lee, DH et al, 2002 in ECs. ECs that are exposed to oxidative stress incur both DNA fragmentation and membrane PS externalization during exposure to insults, such as hypoxia, oxidants, and free radicals (Aoki, M et al, 2001, Burlacu, A et al, 2001, Lin, SH and Maiese, K, 2001). …”
Section: Oxidative Stress and Alzheimer's Diseasementioning
confidence: 99%